1993
DOI: 10.1016/0550-3213(93)90682-f
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and asymptotic scaling in the SU(2) gauge theory

Abstract: We determine the critical couplings for the deconfinement phase transition in SU (2) gauge theory on N τ × N 3 σ lattices with N τ = 8 and 16 and N σ varying between 16 and 48. A comparison with string tension data shows scaling of the ratio T c / √ σ in the entire coupling regime β = 2.30 − 2.75, while the individual quantities still exhibit large scaling violations. We find T c / √ σ =0.69(2). We also discuss in detail the extrapolation of T c /Λ MS and √ σ/Λ MS to the continuum limit. Our result, which is c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
356
4
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(402 citation statements)
references
References 48 publications
41
356
4
1
Order By: Relevance
“…Here, we will use the data for σa 2 reported in Ref. [60] and a linear interpolation of the logarithm of these data where needed. 2 A value of the lattice spacing in physical units was obtained using the value σ = [440 MeV] 2 for the string tension.…”
Section: Setupmentioning
confidence: 99%
“…Here, we will use the data for σa 2 reported in Ref. [60] and a linear interpolation of the logarithm of these data where needed. 2 A value of the lattice spacing in physical units was obtained using the value σ = [440 MeV] 2 for the string tension.…”
Section: Setupmentioning
confidence: 99%
“…We also use the relation between the critical temperature T c and the (zero temperature) 4D physical string tension σ phys [34] :…”
Section: The 3-dimensional Su(2) Georgi-glashow Model On the Latticementioning
confidence: 99%
“…For quenched SU (2) it is found that the universality class is that of the 3d ising model, and ν = .62 [6]. For quenched SU (3) the transition is weak first order [7] and ν = 1/3.…”
Section: Introductionmentioning
confidence: 94%